Biomineralization 2008
DOI: 10.1002/9780470986325.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Biomineralization and Biodemineralization

Abstract: In order to understand the fundamental processes leading to biomineralization, this chapter focuses on the earliest events of homo/heterogeneous nucleation from an initial supersaturated solution phase and subsequent growth involving various possible precursor phases (amorphous or crystalline) to the final mineral phase by specific template and other influences. We also discuss how the combination of macroscopic constant composition and microscopic atomic force microscopy provides insights into the physical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 130 publications
0
18
0
Order By: Relevance
“…57–60 It is reported that amorphous calcium phosphate (ACP) will be formed first at a highly supersaturated calcium phosphate solution, followed by the conversion of ACP into HAP. 61, 62 Since non-mineralized SIS membranes are amorphous, it is difficult to judge the formation of ACP at the very beginning of the mineralization by using XRD. However, according to the reported theory, 61, 62 it is likely that the HAP crystals formed on the SIS membranes were rapidly converted from ACP formed at the very beginning of the biomimetic mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57–60 It is reported that amorphous calcium phosphate (ACP) will be formed first at a highly supersaturated calcium phosphate solution, followed by the conversion of ACP into HAP. 61, 62 Since non-mineralized SIS membranes are amorphous, it is difficult to judge the formation of ACP at the very beginning of the mineralization by using XRD. However, according to the reported theory, 61, 62 it is likely that the HAP crystals formed on the SIS membranes were rapidly converted from ACP formed at the very beginning of the biomimetic mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…61, 62 Since non-mineralized SIS membranes are amorphous, it is difficult to judge the formation of ACP at the very beginning of the mineralization by using XRD. However, according to the reported theory, 61, 62 it is likely that the HAP crystals formed on the SIS membranes were rapidly converted from ACP formed at the very beginning of the biomimetic mineralization. Previous studies 11, 12, 37 have also demonstrated that both HAP-supersaturated solution and 1.5 SBF can induce heterogeneous nucleation when the solution is in direct contact with a foreign substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In solutions, ACP is readily converted to stable crystalline phases such as OCP or apatitic products. One biomineralization strategy that has received significant attention is mineralization via transient precursor phases [135]. …”
Section: Transient Precursor Phasesmentioning
confidence: 99%
“…Glimcher reviewed the state of affairs in 1984 and concluded that whereas there was no evidence that ACP is a mature phase in bone, the possibility that it is a precursor phase in bone formation could not be excluded [136]. The transient ACP phase may conceivably be deposited directly inside the gap regions of collagen fibrils, but it may also be delivered as extrafibrillar particles [135]. This is consistent with the observation of collagen mineralization via a transient ACP precursor phase in vitro to produce aligned intrafibrillar carbonated apatite crystals [144].…”
Section: Transient Precursor Phasesmentioning
confidence: 99%
“…In solutions, ACP is readily converted to stable crystalline phases such as octacalcium phosphate or apatitic products. One biomineralization strategy that has received significant attention in recent years is mineralization via transient precursor phases [16]. Transient amorphous mineral phases have been detected in biomineral systems in different phyla of the animal kingdom [17].…”
Section: Acp In Biomineralizationmentioning
confidence: 99%